Study on Resonance Mechanism and Suppression Scheme of Railway Based on Hefei-Bengbu Line - YE Tao (机车电传动)
Taking Hefei-Bengbu line as an example, the resonant characteristics of the traction power supply system were analyzed theoretically. It was proved that the harmonics were related to the length of the supply arm, locomotive location, characteristics impedance of the contact line, transmission coefficient and the equivalent impedance of traction substation. On this basis, the simulation model of traction power supply system was established. And the frequency characteristics, current and voltage were tested. Based on the analysis of the influence factors of resonance characteristics, the corresponding suppression measures were proposed. In the early stage of the power supply system design,the optimal design of the power supply system according to the matching condition of the vehicle network could destroy the basic condition of resonance,and achieve the purpose of inhibiting resonance.